Legality of United Nations Resolutions on the Restriction of the Use of Nuclear Weapons by States of Legality - Matakena, Jenesya Susye; Wattimena, Josina Augustina Yvonne; Daties, Dyah Ridhul Airin (Balobe Law Journal, 2025)
Introduction: Countries' non-compliance with UN resolutions regarding the prohibition of testing and use of nuclear weapons is due to the position of the resolution which is still classified as Soft Law due to the presence of elements that violate it and are less binding. The use of nuclear weapons can also threaten human life, thereby giving rise to international state responsibility as regulated in the Draft Articles on Responsibility of States for Internationally Wrongful Act.Purposes of the Research: The aim of this research is to examine the legality of the UN resolution on spreading the use of nuclear weapons and the relationship between the Draft Articles on Responsibility of States for Internationally Wrongful Act and the UN resolution.Methods of the Research: The method used is normative juridical with a problem approach, namely a regulatory, case and context approach. Sources of legal materials are primary, secondary and tertiary legal materials. Legal material collection techniques use library research and qualitative analysis.Results of the Research: The legality or binding power of UN General Assembly resolutions is found in three approaches, namely the Customary Law Approach, New Souce Approach, Grey Zone or Soft Law and the legality or binding force of UN Security Council resolutions and the existence of moral force. The relationship between UN resolutions and the Draft Articles on Responsibility of States for Internationally Wrongful Act was established to prevent actions that are not in accordance with international law, so that UN Security Council resolutions can be the basis for state accountability if there are indications of non-compliance with sanctions issued by the Security Council.